2022
DOI: 10.1161/hypertensionaha.122.20048
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Renal Pelvic Denervation: A Feasibility Trial in Patients with Uncontrolled Hypertension

Abstract: Background: Endovascular renal denervation reduces blood pressure (BP). We explored an alternative approach to renal denervation using radiofrequency energy delivered across the renal pelvis utilizing the natural orifice of the urethra and the ureters. Methods: This open-label, single-arm feasibility study enrolled patients with uncontrolled hypertension despite antihypertensive drug therapy. The primary effectiveness endpoint was the change in ambulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Automated office systolic blood pressure, as reported previously [9], fell from a mean value of 156.5 ± 12.3 mm Hg by 22.8 (−30.2, −15.5) by month 2. We now report that it fell (compared with baseline) by 19.8 (−27.2, −12.4) by 6 months, and by 24.8 (33.2, 16.3) by 12 months.…”
Section: Effects On Office Blood Pressuresupporting
confidence: 78%
See 2 more Smart Citations
“…Automated office systolic blood pressure, as reported previously [9], fell from a mean value of 156.5 ± 12.3 mm Hg by 22.8 (−30.2, −15.5) by month 2. We now report that it fell (compared with baseline) by 19.8 (−27.2, −12.4) by 6 months, and by 24.8 (33.2, 16.3) by 12 months.…”
Section: Effects On Office Blood Pressuresupporting
confidence: 78%
“…As previously described [9], 41 patients signed informed consent, 10 did not meet blood pressure entry criteria, 2 were excluded by Covid, and 1 with ureteral stenosis who declined the option of an initial dilation procedure was also excluded. Of the 20 patients who underwent the procedure, only 2 were not receiving Blood Pressure Effects of Renal Pelvic Denervation Am J Nephrol 2024;55:319-328 DOI: 10.1159/000533569 antihypertension therapy, and so were not included in this analysis.…”
Section: Patient Dispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transurethral approaches to renal denervation are also in development and show initial promise. Although sham-controlled studies have not yet been performed, radiofrequency ablation from within the renal pelvis has the potential to reduce BP in patients with hypertension [4].…”
Section: Devicesmentioning
confidence: 99%
“…The ultimate effect of ablating the renal nerves is interrupting both the afferent signals from the kidney to the brainstem and the efferent signals from the brainstem to the kidney. As suggested by the authors in their original publication, it may be mainly ablation of afferent signals from the kidney to the brainstem that is responsible for the early (2 months) responses in blood pressure [2], with the eventual result of a reduction in brainstem sympathetic outflow. The transurethral route undertaken in the Weber study showed an impressive daytime ambulatory systolic blood pressure response at 2 months, sustained at 12 months, of 19 mm Hg.…”
Section: One More Step In the Renal Denervation Trekmentioning
confidence: 99%